2016
DOI: 10.9743/jir.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Podcasting: Perspectives on Pedagogy

Abstract: of podcasting on student learning and engagement, and possibilities for future development in this area. postulate that podcasting complements a Constructivist approach in the classroom, provide much of the research foundation for this paper. The connection between podcasting information in multiple singleeducational podcasting between instructors and students are many. The unique marriage of practical offer single-concept-themed lectures on-the-go, personalized narrative feedback, and gentle guidance to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…In particular, the goal of this podcast was to facilitate student learners to actively construct their own knowledge and meaning from listening, for example applying learning from this podcast to their past personal or professional experiences in healthcare. This underpinning constructivist theory is a popular pedagogical approach which has previously been aligned to podcasting in higher education [37]. Recent literature reviews on podcasting within nursing and medical education have found only a small number of studies were underpinned by a pedagogical theory or alternative learning framework [36,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the goal of this podcast was to facilitate student learners to actively construct their own knowledge and meaning from listening, for example applying learning from this podcast to their past personal or professional experiences in healthcare. This underpinning constructivist theory is a popular pedagogical approach which has previously been aligned to podcasting in higher education [37]. Recent literature reviews on podcasting within nursing and medical education have found only a small number of studies were underpinned by a pedagogical theory or alternative learning framework [36,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of cognitive information in this manner by the new-millennial student clearly identifies the style of learning that supports their interaction with technology. These students embrace digital technology and all the benefits of data transfer rates, rich images, informative video, rapid communication and speed of delivery for varying file sizes (Chen and Wu 2015;Hadie et al 2018;Palenque 2016). Research reported by Palenque (2016) relating to single idea podcasts that create a series of related material suggested that the delivery of information in this manner would enhance student learning.…”
Section: Discussionmentioning
confidence: 99%
“…These students embrace digital technology and all the benefits of data transfer rates, rich images, informative video, rapid communication and speed of delivery for varying file sizes (Chen and Wu 2015;Hadie et al 2018;Palenque 2016). Research reported by Palenque (2016) relating to single idea podcasts that create a series of related material suggested that the delivery of information in this manner would enhance student learning. Further research has also highlighted the decline in learning performance as demonstrated by unit exam results based on traditional didactic lectures when compared with engaging lecture methods that include small breaks (Miller, Mcnear, and Metz 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Audio media have been useful as a way of driving innovation in teaching and health promotion. In teaching, podcasting has been found to be helpful in differentiating forms of learning, providing additional support to students who have specific learning needs, and also foster a sense of inclusivity and belonging to a learning community 11. The use of audio media has also been beneficial for instructors by cutting down on the time needed to provide feedback for students 12.…”
Section: Introductionmentioning
confidence: 99%